Importance of Soft Skills for Graduates in the Real Estate Programmes in Malaysia - Mohd Adnan, Yasmin; Daud, Md Nasir; Alias, Anuar; Razali, Muhammad Najib (Journal of Surveying, Construction and Property, 2017)
The current employment market in Malaysia requires the graduates to be more workplace competent, hence requiring the necessary soft skills. This paper attempts to highlight the key soft skills that have been identified by the Ministry of Higher Education (MOHE), Malaysia in its move to enhance graduates’ employability. To incorporate these soft skills in the undergraduate programmes at universities, MOHE has suggested the following implementation methods to enhance these soft skills for the undergraduate programmes at universities. They are development of soft skills by embedding it in the existing syllabus, the development of soft skills through stand-alone subject, development of soft skills based on campus life, development of soft skills on support programmes, soft skill finishing schools, development of soft skills base on formal and informal activities at faculty levels, and lastly industrial training. Views from the industry are sought to provide an indication of the importance of the identified key soft skills in the real estate area so as to make the necessary emphasis on the curriculum development. Keywords: Undergraduates, employability, soft skills, real estate